The Influence Of Training And Work Motivation On Employee Performance In The Dinas Lingkungan Hidup Kabupaten Pesisir Barat - Wati, Shinta Puspita; Parela, Epi (Universitas Dehasen Bengkulu, 2025)
Based on observations at the Dinas Lingkungan Hidup Kabupaten Pesisir Barat, employee performance has not been optimal, as can be seen from the achievement of performance indicator targets which have not been maximized. This is thought to be caused by the visible phenomenon that the training given to employees is still not good enough in terms of quantity and quality. Apart from that, another problem is low employee motivation in terms of enthusiasm for doing work so that work often cannot be completed as planned.The purpose of this research is to determine the influence of work motivation training on employee performance. The hypothesis in this research is that there is an influence of work motivation training, both partially and simultaneously, on employee performance. The sample in this study consisted of 30 employees. Data collection techniques include observation, documentation and questionnaires. The data analysis method uses a quantitative approach with the help of SPSS version21.0 statistical tools including calculation of validity tests, reliability tests, simple and multiple linear regression tests, t tests, F tests and coefficient of determination tests.The results of hypothesis testing show that training partially has a positive influence on performance with a contribution of 50.1%. Work motivation has a positive influence on performance with a contribution of 45.6%. Simultaneous hypothesis testing shows that work motivation training together has a positive influence on performance with a contribution of 56.5%, while the remaining43.5% is a variation of other variables outside this research. The implication conveyed in this research is that independent internal training activities need to be pursued by management, the leadership element should be more intensive in providing direct direction to employees in carrying out their duties and work, the leadership element can be more intensive in carrying out the supervision function to their subordinates, especially regarding the utilization of work time as influenceively as possible.